Students' Opinions on the Success of the Use of Indonesian Language in Communication within the Campus Environment of STIE El Hakim Sulit Air Solok - Hakim, Afri Mardani (The Future of Education Journal, 2025)
With the rapid advancement of technology, communication has increasingly shifted to digital platforms, especially through mobile phones. The use of the Indonesian language, which is commonly used for communication, has also shifted. The influence of digital language has become a habit, especially among university students. This study aims to raise awareness and understand the effectiveness of the Indonesian language as a means of communication in the campus environment from the perspective of students. Observations were made directly using questionnaires, which were distributed online during the data collection process. The results obtained from 55 students at STIE EL HAKIM indicate that Indonesian is highly effective in campus communication, particularly during classroom learning and outside the classroom, such as in group work and organizational activities. Ultimately, despite the widespread use of informal language in the digital world, students still feel the need to use proper and correct Indonesian in the learning and teaching process and in communication among students, especially since the students come from various regions, allowing Indonesian to facilitate smooth communication.